Place and maps: a cartographic essay on "Orillas del Sar", by Rosalía de Castro - Cabo Aseguinolaza, Fernando (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
This article is focused on the notion of literary cartography to make a critical reading of what has been called Geographical Information Systems of Place. Next, he performs a reading of a poem by Rosalía de Castro to offer some possibilities of analysis of the literary place.
Keywords: literary cartography; place; Geographical Information Systems of Place; Rosalía de Castro